"Doing Men's Jobs": A Commentary on Work–Life Balance Issues Among Women in Engineering and Technology. Issue 1 (June 2019) - Maji, Sucharita
Despite a steep increase in female representation in the workforce in the last decade, the gendered division of labour in the family remains broadly unaltered. Women, even who work for the same duration as their husbands in the office and contribute equally or more to the financial status of the family, often take most of the shares of childcare responsibility and domestic work. Work–family conflict is a global problem for working men and women; the struggle is even more prominent among working women, especially those who work in male-dominated sectors such as engineering and technology. Working in gender-atypical professions, females in engineering and technology face solo status and experience perceived discrimination and social identity threat. They require to put additional efforts to adjust to the work environment which, in turn, impacts their work–life balance status. The gendered work culture in engineering and technology sectors is reported to be masculine and patrifocal as a result of the skewed sex-ratio. Moreover, the study attempted to find out how the gender-role perception and identification of them, gender stigma consciousness, and role conflict may further aggravate the work–family conflicts among women engineers. In addition, the added responsibilities and conflicts that come with motherhood and their impacts on the work–life balance are discussed.